2020
DOI: 10.1515/nanoph-2020-0239
|View full text |Cite
|
Sign up to set email alerts
|

Tunable photoluminescence properties of selenium nanoparticles: biogenic versus chemogenic synthesis

Abstract: AbstractVarious technological and biomedical applications rely on the ability of materials to emit light (photoluminescence [PL]), and, among them, metal nanoparticles (NPs) and semi-conductor Quantum Dots (QDs) represent ideal candidates as sensing probes and imaging tools, portraying better PL features than conventional organic dyes. However, the knowledge of PL behavior of semiconductor NPs – i.e., selenium; SeNPs – is still in its infancy, especially for those synthesized b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 83 publications
(143 reference statements)
4
39
0
Order By: Relevance
“…Undoubtedly, such differences in the absorption profiles of NPs clearly indicate the influence of the intrinsic environments of these RTILs on the formation of Se NPs with significantly different optical properties and morphological features. Various researchers in the recent past have also reported a strong correlation between the optical properties of Se NPs and their morphologies. ,, ,, …”
Section: Results and Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Undoubtedly, such differences in the absorption profiles of NPs clearly indicate the influence of the intrinsic environments of these RTILs on the formation of Se NPs with significantly different optical properties and morphological features. Various researchers in the recent past have also reported a strong correlation between the optical properties of Se NPs and their morphologies. ,, ,, …”
Section: Results and Discussionmentioning
confidence: 97%
“…Various methodologies could be found in the literature regarding the synthesis of Se NPs. Some of the common strategies are solvothermal, radiation-based, biogenic, laser ablation, sonochemical, and microwave-assisted. , However, there are very few reports showing fine control over the morphology as well as phase of Se NPs. ,, In addition, the application of such protocols is further limited by the low stability of α-Se NPs (especially in colloidal form) undergoing rapid phase transformation. Moreover, in the current scenario, the main focus is toward developing such protocols that are green and sustainable for catering to commercial requirements.…”
Section: Introductionmentioning
confidence: 99%
“…In general, depending upon the intensity of a particular peak, one can estimate the type of Se formed. Piacenza et al 107 suggested the use of biologically synthesized SeNPs in bio-imaging. They synthesized SeNPs from yeast extract which exhibited a strong photoluminescence emission in the blue-red region of the visible spectrum and a luminescence lifetime comparable to those of mostly used fluorophores.…”
Section: Synthesis Methodsmentioning
confidence: 99%
“…cultures from dark yellow to orange-red (Figure 1). This phenomenon is due to the development of exciton resonance within Se atoms, which determines the rising of unique optical properties as a function of the size and shape of SeNMs, as well as their surrounding environment [26]. Micrococcus sp.…”
Section: Characterization Of Biogenic Senpsmentioning
confidence: 99%